KRITIK SOSIAL TERHADAP KETIDAKADILAN PADA LIRIK LAGU “BONGKAR” KARYA IWAN FALS - Yuyun Yunengsih; Desma Yuliadi Saputra; Rina Andriani (Nindikayla Institute, 2026)
This study aims to identify forms of social criticism that depict injustice, as found in the lyrics of the song